Effect of the winglet on reduction of blade tip vortex from elliptical hydrofoil. Issue 1 (June 2021) - Maeda, S; Sano, T; Iino, M; Farhat, M; Amini, A
Abstract: It is well known that the performance of the turbomachinery (losses, vibrations, noise, and erosion) is often affected by the trailing vortex from the blade tip (Tip Leakage Vortex; TLV) of the impeller or propeller, and sometimes cavitation occurs in the center of the vortex core (Tip Vortex Cavitation; TVC). Many researches on the vortex characteristics of isolated hydrofoil by numerical simulations or experiments have been done so far, however, the research on understanding the mechanism of the vortex control technique is not enough, and it is important to mitigate the effect of TLV or TVC, to enhance the performance of turbomachinery. In this study, numerical simulation and experimental investigation were carried out to clarify the effect of winglet, attached to the elliptical hydrofoil (NACA16020). Five different winglet patterns were tested, changing bending angle and direction. Experiments were carried out using the high-speed cavitation tunnel in Ecole Polytechnique Fédérale de Lausanne (EPFL). As for numerical simulation, it was carried out in the same condition of the experiment. As a result, it was clarified that TVC decreased as increasing the bending angle of winglet, and disappeared in the case of 90 degree bent toward pressure side. And it is clarified that the vortex strength, in other word, vortex core pressure is affected by the interaction of the leading edge vortex and the tip vortex, and in case of pressure side 90 degree bended winglet, both vortices were mutually affected and cancelled the strength of these vortices.